Job Satisfaction as Mediation in Relationship of Work Life Balance and Work Stress on Employee Performance of Coffeshop in Semarang - Fia Aurelia Andian; Ana Kadarningsih (International Forum of Researchers and Lecturers, 2025)
This study analyze the role of job satisfaction in mediating the relationships between work-life balance (WLB), work stress, and employee performance among Generation Z employees in Semarang coffee shops. Using a quantitative survey approach, data were collected from 151 full-time employees aged 17-27 years across 20 coffee shops. The findings indicate that WLB positively and significantly influences both employee performance and job satisfaction. Additionally, job satisfaction has a direct positive impact on employee performance and mediates the relationship between WLB and performance. Conversely, work stress was found to have no significant direct or indirect effect on performance or satisfaction. These results highlight the critical role of WLB and job satisfaction in enhancing employee productivity, while the impact of work stress appears minimal in this context. Coffee shop management is encouraged to implement flexible policies supporting WLB and to foster job satisfaction.